EVALUASI IMPLEMENTASI TEKNOLOGI INFORMASI PERGURUAN TINGGI MENGGUNAKAN MODEL COBIT FRAME WORK - Sahfitri, Vivi (JURNAL ILMIAH MATRIK, 2014)
Information technology management is processes and structures that control and direct relationship of a companys organization in achieving the organizations goals by adding value that information technology and the process can be balanced with the risks . This study will result in recommendations that information technology in organizations , specially information technology services in the academic private college in the city of Palembang , where the activities of the academic services are the responsibility of integrated service unit of each college . The design of information technology in this study using the COBIT framework version 4.0 . The chosen domain is the domain Deliver and Support ( DS ) and Monitor and Evaluate ( ME ) is intended to make information technology management recommendations.